2008
DOI: 10.11646/zootaxa.1846.1.3
|View full text |Cite
|
Sign up to set email alerts
|

The systematics and biology of Cotesia nonagriae (Olliff) stat. rev. (Hymenoptera: Braconidae: Microgastrinae), a newly recognized member of the Cotesia flavipes species complex

Abstract: The Australian species Cotesia nonagriae Olliff stat. rev. (Hymenoptera: Braconidae) is redescribed and formally removed from synonymy with C. flavipes based on molecular, morphological and biological differences. The taxonomic history and phylogenetic relationships of C. nonagriae with other members of the C. flavipes complex are presented and underscore the importance of molecular-based identification within this group. The biology of C. nonagriae on the native noctuid stemborer host, Bathytricha truncata (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 43 publications
2
23
0
2
Order By: Relevance
“…C. typhae adult longevity was close to that of C. sesamiae , i.e. a mean longevity of about three days when fed honey at 25° and 60% RH (Sallam et al 2002), but shorter than the longevity recorded in similar conditions for C. flavipes (about 5-6 days, Potting et al 1997) and for C. nonagriae (about 12 days, Muirhead et al 2008). Longevity in outdoor conditions may be longer due to cooler temperatures at night and the opportunity to rest in favorable micro-niches provided by plants.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…C. typhae adult longevity was close to that of C. sesamiae , i.e. a mean longevity of about three days when fed honey at 25° and 60% RH (Sallam et al 2002), but shorter than the longevity recorded in similar conditions for C. flavipes (about 5-6 days, Potting et al 1997) and for C. nonagriae (about 12 days, Muirhead et al 2008). Longevity in outdoor conditions may be longer due to cooler temperatures at night and the opportunity to rest in favorable micro-niches provided by plants.…”
Section: Discussionmentioning
confidence: 66%
“…With regard to realized fecundity, data available for the species complex were mostly the number of offspring produced from the first oviposition, which can be estimated at 60 offspring in C. typhae . This value is intermediate between higher value observed for C. nonagriae (about 90 offspring from one oviposition, Muirhead et al 2008), and lower value observed for C. sesamiae and C. flavipes (from 25 to 45, depending on both parasitoid strain and host species, Jiang et al 2004, Mochiah et al 2001, NgiSong et al 1998, Sallam et al 2002). Altogether, these data indicate an evolution of the reproduction strategy within the flavipes complex.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations